A New Species Of Leposoma (Squamata, Gymnophthalmidae) from the remnant atlantic forests of the State of Bahia, Brazil - Miguel Trefaut; Marianna; Dante; Vanessa Kruth (Papéis Avulsos de Zoologia, 2002)
.